Broadband Internet adoption and utilization in the inner city: A comparison of competing theories. (October 2015) - Tsai, Hsin-yi Sandy; LaRose, Robert
Highlights: Examining the efficiency of several technology adoption theories/models. Sufficiency of the social cognitive model of broadband adoption is supported. The SCT model accounts for 52% of the variance in broadband intentions. The SCT model appears to be superior to MATH and UTAUT2. Price sensitivity is a significant predictor of broadband intentions. Abstract: Factors influencing the adoption and utilization of technology have been extensively studied within a variety of theoretical paradigms but questions about their parsimony and their integrations with and contributions to overarching models of human behavior have been questioned. The present research employed a mail survey of inner city residents of a Midwestern state to analyze the sufficiency of the social cognitive theory (SCT) model of broadband adoption by testing it against variables drawn from the Model of Adoption of Technology in Households, Diffusion of Innovations, and the Unified Theory of the Acceptance and Utilization of Technology-2. The variables tested explained little additional variance in broadband intentions after accounting for SCT and demographic variables, arguing for the superior parsimony of the SCT model. Price sensitivity, often overlooked in adoption research, was a significant predictor of broadband intentions and its effect was interpreted through the SCT framework.